Codisposição de lodo de fossa séptica em aterro sanitário do tipo trincheira - Souza, Patrícia Caldeira de (2015)
Given the problematic situation of basic sanitation in Brazil, where many regions are not served by sewage systems, one of the alternatives of the municipalities is to use Individual and Household Sewage Disposal (SITDE), attached as an option for the disposal of domestic sewage. The Residue of Fossa and Septic Tank (RFTS), generated in SITDE is intended, for the most part Sewage Treatment Station (ETE). However, not all municipalities have ETE and due to high load of pollutants and pathogenic organisms in RFTS, there must be an alternative to its proper destination in order to ensure the quality of the environment and preserve public health. Therefore, this study aimed to evaluation of codisposição of RFTS impacts with Urban Solid Waste (RSU) in landfills trench type. For this, four experimental cells were built in the open in the area of the landfill in the city of Goiânia, to receive the following sludge percentage: 0%, 2%, 5% and 9%. Based on the individual volume of the trenches (5 m3), set up an array of 40 kg/day of RSU in each trench, three times a week for five months, from April to August 2013. After the release of RSU in the trenches, they were compressed manually, RFTS codisposto on waste and later it was used to cover the ground. The RFTS used in the study was characterized according to the parameters pH, Biochemical Oxygen Demand (DBO), Chemical Oxygen Demand (DQO), total solids, fixed total solids, total volatile solids, total suspended solids, fixed suspended solids, volatile suspended solids, sedimented solids, turbidity, ammonia nitrogen and total phosphorus. The results showed that the moisture content of RSU grounded to a depth meter increased with the incubation time, and the volatile solids remained constant. In quantitative terms, the sludge codisposition in different percentages did not affect the volume of leachate generated. As to the quality of the leachate, there was an increase in total solids concentrations for the parameters, COD, BOD and ammonia nitrogen in the trenches receiving cavity residues and septic tank, in particular at concentrations of 5 and 9%. The presence of total coliforms and Escherichia coli was stabilized in very close values with the passage of time in all trenches do not indicate a long-term impact. For pH, who always remained in the alkaline range, the addition of the sludge did not result in changes considered significant. It is recommended to carry out further studies adopting other levels of pit residue concentrations and septic tank trench in landfills.